Roadmap for an imaging and modelling paediatric study in rural NZ - Kumar, Haribalan; Green, Robby; Cornfeld, Daniel M.; Condron, Paul; Emsden, Taylor; Elsayed, Ayah; Zhao, Debbie; Gilbert, Kat; Nash, Martyn P.; Clark, Alys R.; Tawhai, Merryn H.; Burrowes, Kelly; et al. (Frontiers in Physiology, 2023)
Our study methodology is motivated from three disparate needs: one, imaging studies have existed in silo and study organs and not across organ systems; two, there are gaps in our understanding of paediatric structure and function; three, lack of representative data in New Zealand. Our research aims to address these issues in part, through the combination of magnetic resonance imaging, advanced image processing algorithms and computational modelling. Our study demonstrated the need to take an organ-system approach and scan multiple organs on the same child. We have pilot tested an imaging protocol to be minimally disruptive to the children and demonstrated state-of-the-art image processing and personalised computational models using the imaging data. Our imaging protocol spans brain, lungs, heart, muscle, bones, abdominal and vascular systems. Our initial set of results demonstrated child-specific measurements on one dataset. This work is novel and interesting as we have run multiple computational physiology workflows to generate personalised computational models. Our proposed work is the first step towards achieving the integration of imaging and modelling improving our understanding of the human body in paediatric health and disease.